SYSTEMATIC LITERATURE REVIEW: THE EFFECTIVENESS OF PROJECT BASED LEARNING AND EXPERIENTIAL LEARNING MODELS IN FOSTERING HIGH SCHOOL STUDENTS' ENTREPRENEURIAL INTENTION - Rianzah Munawaroh; Eni Noviani; Wening Patmi Rahayu; Andy Prasetyo Wati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This Systematic Literature Review (SLR) aims to identify, evaluate, and synthesize the most effective and relevant learning models for Entrepreneurship subjects at the Senior High School (SMA) level. Specifically, this review focuses on the effectiveness of project-based and experiential learning models in enhancing students' entrepreneurial intention and practical skills. This systematic review was conducted based on the PRISMA framework. The literature search was performed on academic databases such as Scopus, Google Scholar, and ERIC, with publications restricted to the years 2018 to 2025. The inclusion criteria required articles to be empirical research focusing on entrepreneurship learning models within the SMA/MA context. A total of 15 articles met the criteria, and their data were extracted for thematic-qualitative analysis. The findings indicate that the Project-Based Learning (PjBL) and Experiential Learning (EL) models are the dominant and significantly effective approaches. PjBL is effective in improving business planning and product skills, while Experiential Learning excels at fostering the entrepreneurial mindset, attitude, and self-reliance. A key research gap identified is the lack of active collaborative integration with real business practitioners. Entrepreneurship learning at the high school level must be designed using applicable and contextual models. The integration of PjBL and Experiential Learning should be optimized to bridge the gap between theory and practice effectively.